Pretreatment Hemoglobin Level Is an Independent Prognostic Factor in Patients with Lung Adenocarcinoma. (15th May 2018) - Zhang, Yue-Hua; Lu, Yuquan; Lu, Hong; Zhang, Meng-Wei; Zhou, Yue-Min; Li, Xiang-Lei
Abstract : Background/Aim . Few studies have reported the prognostic value of pretreatment hemoglobin levels in patients with lung adenocarcinoma (LA). In the present study, we retrospectively reviewed 306 LA patients for their prognosis associated with the pretreatment hemoglobin levels. Methods . Person-years and case fatality rate (CFR) were calculated from May 2010 to June 2017. Hazard ratio (HR) and 95% confidence intervals (CIs) were estimated using the Cox proportional hazards regression analysis. Survival curves were generated using the Kaplan–Meier analysis. Results . Patients with low pretreatment hemoglobin (LPHb) levels had a higher CFR than did patients with normal pretreatment hemoglobin (NPHb) levels (HR = 1.48, 95% CI = 1.06–2.08, andP = 0.023 ). Overall survival of NPHb patients was significantly higher than that of LPHb patients (P < 0.05 ). Conclusion . Low pretreatment hemoglobin level was demonstrated to be an independent biomarker for poor prognosis in patients with LA.